The courage to be: Paul Tillich's existentialist theology of the cross in relation to Martin Luther. Issue 3 (2nd September 2018) - Jennings, Brach S.
Abstract: Paul Tillich is a traditionally rooted, yet progressive, theologian and philosopher who sought to bring the Christian message to the predicament of existential meaninglessness faced by modern people. The present article addresses a scholarly gap by emphasizing Tillich's use of Martin Luther's theology of the cross, in order to demonstrate Tillich's theological relevance for today from a Lutheran lens.